Euro area banks' interest rate risk exposure to level, slope and curvature swings in the yield curve - Daniel Foos; Eva Lütkebohmert; Mariia Markovych; Kamil Pliszka (Deutsche Bundesbank, 2017)
This paper investigates interest rate risk exposures of listed euro area banks which fall under the Single Supervisory Mechanism (SSM). We analyze the period 2005 to 2014, as it includes times of very low interest rates in which banks may have pursued a more risky maturity transformation strategy. First, we use the Bayesian DCC M-GARCH model to assess banks' stock price sensitivities to principal components of changes in the yield curve describing shifts in its level, slope and curvature. Second, we investigate how these sensitivities vary depending on bank-level characteristics (e.g., balance sheet composition, reliance on interest income). Our findings reveal that, on average, banks benefit from positive level shifts and steepening yield curves. Curvature changes affect banks' share prices as well, particularly in times of crises. Further, these sensitivities change in time and depend heavily on the bank's business model and balance sheet composition. Our analysis reveals that banks with larger balance sheets, higher capital ratios, higher parts of customer loans and lower parts of deposits are particularly sensitive to interest rate movements.
Keywords: C11; C51; C55; 330; Bayesian DCC M-GARCH model; interest rate risk; maturity transformation; swings in the yield curve